Local Wisdom, Islamic Law, and Criminal Law in Higher Education: A Preventive Framework against Bullying through Pangadereng Culture and a Compassion-Based Curriculum - Nawawi, Jumriani; Lisma; Aris, Ismail; Hamzah; Nursyam, Andi Resky; Baharuddin, A. Zamakhsyari (Mazahibuna: Jurnal Perbandingan Mazhab, 2026)
In the study of fiqh jināyah, bullying is classified as a jarīmah (criminal act) that threatens the preservation of life (ḥifẓ al-nafs) and protection of dignity (ḥifẓ al-‘irḍ), ultimately leading to the deterioration of human relationships. This study analyzes the implementation of a compassion-based curriculum grounded in Pangadereng values within higher education institutions as a preventive framework (sadd al-żarī‘ah) against bullying. The research employs a qualitative method with phenomenological and fiqh approaches. Primary data were collected through in-depth interviews and observations conducted in four regencies in South Sulawesi, namely Bone, Soppeng, Wajo, and Sinjai. The findings indicate that the harmonization of Pangadereng values within the compassion-based curriculum conceptually occupies the position of ‘urf ṣaḥīḥ, serving as a behavioral guideline for the Bugis community. Empirically, the curriculum has proven effective in preventing bullying by shaping students’ perspectives to promote mutual respect and empathy. The transformation of local wisdom functions as a mechanism to block pathways to criminal behavior in accordance with the concept of sadd al-żarī‘ah and aligns with the objectives of Islamic law within the framework of maqāṣid al-sharī‘ah. This study concludes that integrating local wisdom into character education can serve as a form of Islamic public policy (siyāsah shar‘iyyah) aimed at fostering a more humanistic educational environment. Furthermore, this study enriches the discourse of contemporary fiqh al-jināyah by positioning living societal values as a strategic framework for mitigating violence in academic settings.